Analisis Pengaruh Suasana Toko, Variasi Merchandise, dan Kualitas Pelayanan terhadap Keputusan Pembelian Aksesoris Gadget: Studi Kasus Gerai Wellcommshop Mal Citraland - Nursanti, Tinjung Desy; Herlina, Herlina (Bina Nusantara University, 2012)
The growing technological applications encourage people to use gadgets as the easiest way to connect their daily lives. The demand for gadgets creates new kind of business opportunities. Many companies can produce supporting product such gadget accessories. One company that engaged in the provision of gadget accessories is Wellcomshop. The company is aggressively increasing sales of gadget accessories. Therefore, the company wants to evaluate the variables that influence purchasing decisions of gadget accessories. The purpose of this study is to determine whether there is influence between variables store atmosphere, merchandise varieties, and quality of service in determining purchasing decisions in Wellcomm Accessories Gadget Shop Mall Citraland. This study is an associative research and using a simple method of correlation and multiple regressions. The population in this study is the consumer Wellcommshop Citraland Mall, while the samples are 90 respondents. The results show that the variation of merchandise (x2) and quality of service (x3) has a significant influence on purchase decisions. While, the atmosphere of the store (x1) does not significantly influence purchasing decisions.